Multi-sensor core logger (MSCL) data LU18-1 to LU18-3 - Valentin Nigg; Paola Bacigaluppi; David F Vetsch; Hendrik Vogel; Katrina Kremer; Flavio S Anselmetti (PANGAEA, 2021)
Processed core logging data of core LU18-1 analyzed with a Geotek multi-sensor core logger (MSCL) at the Institute of Geological Sciences, University of Bern. The dataset includes core ID, composite core depth, core thickness, P-wave velocity, density, and magnetic susceptibility.
In: Nigg, V et al. (2021): Shallow-Water Tsunami Deposits: Evidence from Sediment Cores and Wave Propagation of the 1601 CE Lake Lucerne Event [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.938716